Dosimetry Evaluations in Breast Cancer Using 3D-CRT Technique - Ambarsari, Laily Izzati; Irsal, Muhammad; Sutoro, Shinta Gunawati; Apriantoro, Nursama Heru; Winarno, Guntur; Lesmana, Hadi (JURNAL PROTEKSI KESEHATAN, 2024)
Several previous studies have shown that without dose evaluation and monitoring, there is a potential for deterministic radiation effects in 3D-CRT procedures. This study is expected to close the gap by conducting a more comprehensive evaluation of the 3D-CRT technique for breast cancer patients. The research method is quantitative analysis with a study sample of 20 breast cancer patients. Data processing was carried out by conducting statistical tests for the distribution value of organs at risk (OAR) against the Radiation Therapy Oncology Group (RTOG) guidelines and analyzing the conformity index (CI) and homogeneity index (HI) values according to the values recommended by the International Commission Radiation Unit (ICRU). The results of this study obtained OAR doses for the lungs and heart are still within the tolerance value limits set by RTOG p-value <0.05. then for CI and HI there is a deviation p-value <0.05 that there is a difference between the values obtained and the ICRU recommended value. This is due to the location of the target or tumor adjacent to the OAR, to keep the OAR value in accordance with the specified limit value.